Treatment of extraoral sinus tract with endodontic intervention: A case report - (:unkn) unknown (My University, 2020)
Odontejenik fistüller çoğunlukla pulpa enflamasyonuna bağlı gelişen tedavisi için genellikle kanal tedavisi nadiren de cerrahi işlem gereken patolojik oluşumlardır. Pek çoğu intraoral olarak oluşmasına rağmen bazen ekstraoral olarak da gözlemlenebilmektedir. Ekstraoral fistül, ağız boşluğu ve cilt arasında patolojik bir yoldur. Hastaların genellikle dental semptomları olamaması sebebiyle pek çok diğer cilt lezyonu ile karışabilmekte ve etkisiz tedaviler uygulanabilmektedir. Bu sebeple bu vakaların ayırıcı tanısının yapılması oldukça önemlidir. Bu vaka sunumu, alt çene kesici dişlerden oluştuğu tespit edilen ve çene ucu bölgesinden drene ekstraoral fistül vakasının kök kanal tedavisi uygulamasının ardından 3 aylık takibini içermektedir

Odontogenic sinus tracts, mostly caused by pulp inflammation are pathologic formations which usually require root canal treatment and rarely surgical procedures. Although most of them occur intraorally, they may also occur extraorally. An extraoral sinus tract is a pathologic pathway between the oral cavity and the skin which can be confused with many other skin lesions and ineffective treatments may be applied because the patients usually do not have dental symptoms. Therefore, the differential diagnosis of these cases is very important. This case report describes the treatment and 3 month follow-up of an extraoral sinus tract which derives from lower incisors.
Keywords: Deri lezyonları; ekstraoral fistül; kök kanal tedavisi; odontojenik fistül; periapikal lezyon; Extraoral sinus tract; odontogenic fistula; periapical lesion; root canal treatment; skin lessions